STRATEGI MENINGKATKAN KEPUASAN MASYARAKAT TERHADAP PELAYANAN APARATUR DESA CIBADUNG, KECAMATAN GUNUNG SINDUR, KABUPATEN BOGOR - Edi Junaedi; Anugrah Sapto Hadi; Pendi Ahmad (Jurnal Pengabdian Sosial, 2023)
ABSTRACT The purpose of implementing this PKM is that we want to provide training on strategies and knowledge on how to be able to increase community satisfaction with the services of the Cibadung Village apparatus. The participants of this PKM implementation are all staff/apparatus of Cibadung Village, with the aim of providing a higher understanding and conveying guidance in the form of a strategy on how to improve the services of Cibadung Village apparatus and increase the satisfaction of the Cibadung Village community towards the services of Cibadung Village apparatus. We carry out this PKM implementation method in several ways, namely: Providing guidance and training to all Cibadung Village apparatus regarding work discipline and Excellent Service; Provide opportunities for all PKM participants to express opinions, input, suggestions including complaints faced by participants; Open discussion forums, to provide problem solving and solutions to problems faced by all Cibadung village officials. Based on the implementation of observations that we made directly with Partners, the problems encountered were obtained, including the following: There are still some Cibadung village officials whose work discipline still needs to be improved; There are still obstacles for the Cibadung Village apparatus in conveying information to the community with effective communication; and others. For the problems above, the service team submitted several solutions to solve the problems faced by the Cibadung village apparatus, including the following: 1) We, the service team, provided counseling which contained material on strategies to increase community satisfaction in terms of service to the Cibadung village apparatus; 2) We are a team of servants delivering and providing training on how to improve discipline in public services with the hope that community satisfaction will increase; 3) We are a service team providing excellent service training or excellent service to all Cibadung Village apparatus. While the outcomes that the service team wants to obtain from this PKM activity are: 1) There has been an increase in the discipline of the Cibadung Village apparatus; 2) Knowledge of excellent service or excellent service for all Cibadung village apparatus increases; 3) All Cibadung Village apparatus have the ability to handle community complaints and have the expertise to provide solutions. Keywords: Strategic, Public Satisfaction , Services, Village Staff